1993
DOI: 10.1128/jb.175.18.5890-5898.1993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the active site and thermostability regions of endoxylanase from Thermoanaerobacterium saccharolyticum B6A-RI

Abstract: Deletion mutants were constructed from pZEP12, which contained the intact Thermoanaerobacterium saccharolyticum endoxylanase gene (xynA). Deletion of 1.75 kb from the N-terminal end of xynA resulted in a mutant enzyme that retained activity but lost thermostability. Deletion of 1.05 kb from the C terminus did not alter thermostability or activity. The deduced amino acid sequence of T. saccharolyticum B6A-RI endoxylanase XynA was aligned with five other family F beta-glycanases by using the PILEUP program of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 47 publications
2
83
0
2
Order By: Relevance
“…31) Some xylan-binding modules classified in family 22 were originally identified as thermostabilizing modules, because their removal from thermophilic enzymes resulted in decreases in the thermostability and/or optimal temperature of the enzymes. [50][51][52] Removal of the N-terminal CBM27 of Man26 of C. saccharolyticus strain Rt8B.4 resulted in a decrease in the optimal temperature of the enzyme. 53) However, removal of the C-terminal CBM27 region from Man5C of strain MA-138 did not affect its optimal temperature (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…31) Some xylan-binding modules classified in family 22 were originally identified as thermostabilizing modules, because their removal from thermophilic enzymes resulted in decreases in the thermostability and/or optimal temperature of the enzymes. [50][51][52] Removal of the N-terminal CBM27 of Man26 of C. saccharolyticus strain Rt8B.4 resulted in a decrease in the optimal temperature of the enzyme. 53) However, removal of the C-terminal CBM27 region from Man5C of strain MA-138 did not affect its optimal temperature (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The duplicated C-terminal domain belongs to a novel type of cellulose-binding domains (CBDs), also present in modular xylanases from Thermoanaerobacterium saccharolyticurn (Lee et al, 1993). Clostridium thermocellurn (M.Y.…”
mentioning
confidence: 99%
“…Family-22 CBMs were originally identified as thermostabilizing modules, i.e., shifts (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) C) in optimum temperature upon artificial removal of family-22 CBMs from thermophilic modular xylanases were observed in C. cellulovorans XynA (from 90 to 70 C), 8) C. stercorarium Xyn10B (75 to 60 C), 15) C. thermocellum Xyn10C (80 to 60 C), 16) XynX (70 to 60 C), 20) XynY (75 to 60 C), 10) and T. saccharolyticum XynA (75 to 65 C) 13) in the presence of the substrate. Furthermore, an increase in thermostability in the absence of the substrate was observed in C. cellulovorans XynA, C. thermocellum XynX, and C. thermocellum XynX and XynY.…”
Section: Discussionmentioning
confidence: 99%
“…10,13,14) Recently, furthermore, we have found that a truncated derivative of C. stercorarium Xyn10B, composed of two family-22 CBMs and a CM, preferred -1,3-1,4-glucan, such as barley -glucan or lichenan, to xylan as a substrate, and removal of the CBMs from this enzyme drastically reduced catalytic activity toward -1,3-1,4-glucan but not toward xylan, suggesting that the family-22 CBMs in C. stercorarium Xyn10B are a determinant factor for -1,3-1,4-glucanase activity. 15) By contrast, C. thermocellum Xyn10C is less active toward -1,3-1,4-glucan regardless of the presence or absence of a family-22 CBM.…”
Section: )mentioning
confidence: 99%